Significance of Aspergillus niger aggregate species as contaminants of food products in Spain regarding their occurrence and their ability to produce mycotoxins. (September 2019) - Gil-Serna, Jéssica; García-Díaz, Marta; Vázquez, Covadonga; González-Jaén, María Teresa; Patiño, Belén
Abstract: The Aspergillus niger aggregate contains 15 morphologically indistinguishable species which presence is related to ochratoxin A (OTA) and fumonisin B2 (FB2 ) contamination of foodstuffs. The taxonomy of this group was recently reevaluated and there is a need of new studies regarding the risk that these species might pose to food security. 258 isolates of A. niger aggregate obtained from a variety of products from Spain were classified by molecular methods being A. tubingensis the most frequently occurring (67.5%) followed by A. welwitschiae (19.4%) and A. niger (11.7%). Their potential ability to produce mycotoxins was evaluated by PCR protocols which allow a rapid detection of OTA and FB2 biosynthetic genes in their genomes. OTA production is not widespread in A. niger aggregate since only 17% of A. niger and 6% of A. welwitschiae isolates presented the complete biosynthetic cluster whereas the lack of the cluster was confirmed in all A. tubingensis isolates. On the other hand, A. niger and A. welwitschiae seem to be important FB2 producers with 97% and 29% of the isolates, respectively, presenting the complete cluster. The genes involved in OTA and FB2 were overexpressed in producing isolates and their expression was related to mycotoxin synthesis. Highlights: Aspergillus tubingensis is the most frequently isolated species in Spanish products. Aspergillus tubingensis seems not to be able to produce ochratoxin A or fumonisin B2. Most Spanish A. niger and A. welwitschiae isolates are potential mycotoxin producers.